The Influence of ICAM1 3′UTR Gene Polymorphism on the Occurrence and Metastasis of Primary Liver Cancer. (26th November 2021) - He, Li; Wang, Suwen; Ma, Xusheng
Abstract : Objective . In this study, we explored the influence of single nucleotide polymorphism (SNP) in the noncoding region of intercellular adhesion molecule 1 (ICAM1) gene on the occurrence and metastasis of primary hepatocellular carcinoma (PHC). Methods . Sanger sequencing was used to analyze the genotypes of rs3093032, rs923366, and rs281437 locus in the 3 ′ untranslated region (UTR) of the ICAM1 gene. The level of plasma ICAM1 was analyzed by enzyme-linked immunosorbent assay (ELISA). Results . After adjusting for risk factors such as BMI, smoking, drinking, family history of tumors, and hepatitis B virus test results, the CT genotype at rs3093032 of the ICAM1 gene (OR = 0.19, 95% CI: 0.08-0.44, P < 0.01 ), dominance model (OR = 0.23, 95% CI: 0.11-0.48, P < 0.01 ), and T allele (OR = 0.27, 95% CI: 0.14-0.53, P < 0.01 ) were related to the reduced risk of PHC susceptibility. rs923366 locus CT genotype (OR = 0.63, 95% CI: 0.44-0.90, P = 0.01 ), TT genotype (OR = 0.23, 95% CI: 0.10-0.53, P < 0.01 ), dominant model (OR = 0.55, 95% CI: 0.39-0.77, P < 0.01 ), recessive model (OR = 0.28, 95% CI: 0.12-0.62, P < 0.01 ), and T allele (OR = 0.55, 95% CI: 0.42-0.73, P < 0.01 ) were related to a reduction in the risk of PHC susceptibility. rs281437 locus CT genotype (OR = 2.08, 95% CI: 1.40-3.09, P < 0.01 ), TT genotype (OR = 5.20, 95% CI: 2.22-12.17, P < 0.01 ), dominant model (OR = 2.45, 95% CI: 1.69-3.54, P < 0.01 ), recessive model (OR = 4.32, 95% CI: 1.86-10.06, P < 0.01 ), and T allele (OR = 2.46, 95% CI: 1.79-3.38, P < 0.01 ) were significantly related to the increased risk of PHC susceptibility. SNPs at rs3093032, rs923366, and rs281437 of the ICAM1 gene were significantly correlated with TNM stage and tumor metastasis of PHC patients (P < 0.05 ). Conclusion . SNPs at rs3093032, rs923366, and rs281437 in the 3 ′ UTR region of the ICAM1 gene are related to the occurrence and metastasis of PHC.